Effects of Business Risk on Performance on Insurance: A Case Study of Pax Insurance Company Limited - Kenneth Kiptum Tanui (Uganda Christian University, 2023)
The research study aim was to establish the effects of business risk on performance of insurance with specific objectives being; to determine the effects of financial risk management on performances of Pax insurance company limited; to establish the effects of operations risk management on performance of Pax insurance company limited; to establish the effects of risk monitoring on performance of Pax insurance company limited; to determine if insurance firms liquidity effect on performance of Pax insurance company limited. The study will add to the body of literature and researches shall be able to use this research study as a reference to what they will do in future not forgetting that it was used as a source of literature review to their studies. 47 respondents were chosen through random sampling that was stratified. The researcher used secondary information sources which were obtained through reading relevant literature available in the library, various documents, publications and reports including, journals, and magazines. The research questionnaires were administered by the researcher himself respondents Data was analyzed through frequency and descriptive statistics. Data was presented with aid of graphs and pie charts and graphs. The study had the following recommendations based on study findings management of Pax insurance company limited should embrace the use of risk identification process to assist in business risk management in ensuring that prospects are maximized and increase in financial performance. The study conclusion is that insurance firms that poorly manage their risk are always faced with accumulations of claims which lead to increased losses and hence poor performance. Business risk management actions are affected by managers risk behavior, a robust business risk management framework can help companies reduce their exposer to risks and enhance organization performance. Organization that select a particular risk tool tends to be associated with the firm's calculative culture that measures attitudes that managers display towards the use of business risk models.
This is a dissertation.